Analisa Transaksi Spot, Forward dan Swap Sebagai Alat Pengendalian Risiko - Asiah, Siti Nur; Roestiono, Harry (Jurnal Ilmiah Manajemen Kesatuan, 2018)
Risk control is an important step and determines overall risk management. The known risks and their potential consequences must be managed appropriately, effectively, and accordingly company. Risk control is also necessary when foreign exchange transactions are due to currency fluctuations and foreign exchange differences. The exchange rate difference can be obtained from spot, forward and swap transactions we get from spot, forward and swap transactions. The purpose of this research is as follows: 1. To know the procedure of Spot, Forward and Swap foreign exchange transaction at X bank,2. To know the risk control in foreign currency transactions at X bank, 3. To know the analysis of spot, forward and swap transactions as risk control tools at X bank. The research method used in this research is Research Methods Quantitative Descriptive Analysis. With this method facilitate the author in analyzing data from the results described by the author.The results show: spot transactions, certainly will avoid the risk of exchange rate fluctuations because the bank will directly benefit from the spot transactions. And using forward and swap transactions must still be done because to avoid the risk of unexpected exchange rate fluctuations, although there are some larger transactions than forward and swap contracts but negotiations can be done together. Keywords: spot, forward, swap, risk control